Firm pay dynamics - Niklas Engbom; Christian Moser; Jan Sauermann (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2021)
We study the nature of firm pay dynamics. To this end, we propose a statistical model that extends the seminal framework by Abowd, Kramarz, and Margolis (1999a) to allow for idiosyncratically time-varying firm pay policies. We estimate the model using linked employeremployee data for Sweden from 1985 to 2015. By drawing on detailed firm financials data, we show that firms that become more productive and accumulate capital raise pay, whereas firms lower pay as they add workers. A secular increase in firm-year pay dispersion in Sweden since 1985 is accounted for by greater persistence of firm pay among incumbent firms as well as greater dispersion in firm pay among entrant firms, as opposed to more volatile firm pay.
Keywords: J31; D22; D31; E24; M13; 330; Earnings Inequality; Worker and Firm Heterogeneity; Linked Employer-Employee Data; AKM; Two-Way Fixed Effects Model; Firm Dynamics; Vergütungssystem; Lohnstruktur; Schätztheorie; Schweden